Pengaruh Produksi, Harga, Nilai Tukar dan Inflasi Terhadap Ekspor Batu Bara di Indonesia - Rifki Agustiansah; Erni Achmad; Zainul Bahri (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to: 1) Determine and analyze the influence of production, prices, exchange rates, and inflation on coal exports in Indonesia during 2005-2024. 2) Determine and analyze the difference between coal export volume and crude oil export volume in Indonesia during 2005-2024. The data collection method was a survey using a questionnaire. The analysis tools used were Multiple Linear Regression and the Mann-Whitney Test. The results of the multiple linear regression test indicate that prices, production, and exchange rates have a positive and significant effect on coal exports in Indonesia during 2005-2024. Meanwhile, inflation does not have a significant effect on coal exports in Indonesia during 2005-2024. The results of the Mann-Whiney U test indicate a significant difference between coal export volume and crude oil export volume in Indonesia during 2005-2024.